2021
DOI: 10.3390/batteries7030056
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Electrochemical Impedance Spectroscopy on Zinc-Air Batteries Using the Distribution of Relaxation Times

Abstract: Zinc-air batteries could be a key technology for higher energy densities of electrochemical energy storage systems. Many questions remain unanswered, however, and new methods for analyses and quantifications are needed. In this study, the distribution of relaxation times (DRT) based on ridge regression was applied to the impedance data of primary zinc-air batteries in a temperature range of 253 K and 313 K and at different State-of-Charges for the first time. Furthermore, the problem of the regularization para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…From 5 to 3.3 to 2 mA (C/60 to C/90 to C/150, respectively), there were increases in the mass utilisation, from 75.8% to 80.5% to 87.4% of the 300 mAh capacity, respectively (figure 2(e), dark grey bars). Such a rate dependency has also been reported by others [17], thought to arise from increasing resistance resulting from the higher current, which leads to larger internal overpotentials. It could also be due to oxide formation effectively 'blocking' the active material at higher rates, though the exact nature of this relation is complex and dependent on many factors, like electrode thickness, particle size and/or electrolyte concentration [28].…”
Section: Rate-dependency Of Dischargesupporting
confidence: 79%
See 1 more Smart Citation
“…From 5 to 3.3 to 2 mA (C/60 to C/90 to C/150, respectively), there were increases in the mass utilisation, from 75.8% to 80.5% to 87.4% of the 300 mAh capacity, respectively (figure 2(e), dark grey bars). Such a rate dependency has also been reported by others [17], thought to arise from increasing resistance resulting from the higher current, which leads to larger internal overpotentials. It could also be due to oxide formation effectively 'blocking' the active material at higher rates, though the exact nature of this relation is complex and dependent on many factors, like electrode thickness, particle size and/or electrolyte concentration [28].…”
Section: Rate-dependency Of Dischargesupporting
confidence: 79%
“…Furthermore, zinc-air batteries have been shown by electrochemical impedance spectroscopy (EIS) to have a significant rate-dependence, with increasing capacity utilisation with decreasing rate (i.e. longer discharge times) [17]. However, while electrochemical methods like EIS can provide information about the bulk behaviour, they do not provide any information about anode morphology and the changes occurring within the electrode microstructure during discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Franke‐Lang and Kowal showed that for commercial PR48 cells, with 300 mAh at 2 mA constant discharge, an efficiency of about 85% can be achieved. [ 44 ] Hack et al also found this value to be 87% using tomography measurements under the same conditions. [ 46 ] Both highlighted the current dependency, where the discharge capacity decreases dramatically with higher discharge currents.…”
Section: Resultsmentioning
confidence: 90%
“…Five typical DRT peaks corresponding to five substeps, denoted as P1-P5 from high to low frequencies, are identified in the detected frequency range. According to the previously reported literature, 58,59 P1 and P2 peaks are strongly associated with the OH − transportation across the electrode/electrolyte interface; P3 and P4 peaks are mainly related to surface electrode kinetic processes, including the charge transferring process as well as the diffusion and exchange of active reactants (OH -) in the electrodes, whereas P5 peak is possibly ascribed to the Warburg diffusion process, which is predominately intrigued by the O2 − transfer near the electrode/electrolyte interface. Additionally, the enclosed area of each peak in the DRT curve represents the R p of the corresponding substep.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%